The Existence of Gayo Adat Law in Resolving Cases in Kutacane, Southeast Aceh [Eksistensi Hukum Adat Gayo dalam Menyelesaikan Perkara di Kutacane Aceh Tenggara] - Misran Misran (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2020)
Abstract: The Gayo community in Kutacane, Southeast Aceh Regency, does not apply Gayo customary law in resolving disputes. The Gayo community in Kutacane uses the customary law of Alas in resolving all disputes/cases in the community. There are four customary law criteria imposed on perpetrators of customary violators, namely: (1) Opat (four), (2) Waluh Eight, (3) Sixteen, and (4) Tige Due. The amount of this customary fine is following the conditions and agreements or decisions of the customary court. Thus, the existence of Gayo customary law in Kutacane, Southeast Aceh is not realized in the life of the Gayo community. However, the implementation of Kutacane customary law in resolving disputes/cases does not conflict with Islamic law, because the customary law integrates Islamic legal values, namely the principle of peace, the principle of forgiveness, and the principle of eliminating revenge. In addition, it is also following the concept of ta'zir punishment in the theory of Islamic criminal law. Ta'zir punishment is a punishment decided by the leader, to realize the benefit. Abstrak: Masyarakat Gayo di Kutacane Kabupaten Aceh Tenggara, tidak menerapkan hukum adat Gayo dalam menyelesaikan sengketa. Masyarakat suku Gayo di Kutacane menggunakan hukum adat Alas dalam menyelesaikan segala sengketa/perkara dalam masyarakat. Terdapat empat kriteria hukum adat yang dijatuhkan kepada pelaku pelanggar adat, yaitu: (1) Opat (empat), (2) Waluh Delapan), (3) Enam Belas, dan (4)Tige Due. Besaran denda adat ini sesuai dengan kondisi dan kesepakatan atau keputusan peradilan adat. Dengan demikian, eksistensi hukum adat Gayo di Kutacane Aceh Tenggara tidak direalisasikan dalam kehidupan masyarakat Gayo. Namun demikian pelaksanaan hukum adat Kutacane dalam menyelesaikan sengketa/perkara, tidak bertentangan dengan hukum Islam, karena dalam hukum adat tersebut terintegrasi nilai hukum Islam, yakni asas perdamaian, asas kemaafan, asas menghilangkan dendam. Di samping itu, juga sesuai dengan konsep hukuman ta’zir dalam teori hukum pidana Islam. Hukuman ta’zir adalah hukuman yang diputuskan oleh pemimpin, untuk mewujudkan kemaslahatan.